Profile of miRNAs induced during sheep fat tail development and roles of four key miRNAs in proliferation and differentiation of sheep preadipocytes - Zhang, Wei; Wang, Shiyin; Yang, Liwei; Gao, Li; Ning, Chengcheng; Xu, Mengsi; Deng, Shuangyi; Gan, Shangquan (Frontiers in Veterinary Science, 2024)
BackgroundThe fat tail of sheep is an adaptive trait that facilitates their adaptation to harsh natural environments. MicroRNAs (miRNAs) have been demonstrated to play crucial roles in the regulation of tail fat deposition.MethodsIn this study, miRNA-Seq was employed to investigate the expression profiles of miRNAs during different developmental stages of sheep fat tails and elucidate the functions of differentially expressed miRNAs (DE miRNAs).ResultsA total of 350 DE miRNAs were identified, among which 191, 60, 26, and 21 were significantly upregulated in tail fat tissues of fetal, lamb, hogget Altay sheep, and adult Xinjiang fine wool (XFW) sheep but downregulated in other stages. Furthermore, we predicted a set of candidate target genes (4,476) for the top 20 DE miRNAs. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that they involve in several adipogenesis-related pathways. Subsequent investigations indicated that four DE miRNAs, miR-433-3p, miR-485-3p, miR-409-3p, and miR-495-3p, could suppress the expression of peroxisome proliferator-activated receptor gamma (PPARγ) and phosphoinositide-3-kinase regulatory subunit 3 (PIK3R3) and regulate the preadipocyte development in sheep. Meanwhile, the lipid metabolism-related genes, fatty acid-binding protein (FABP3), perilipin 1 (PLIN1), adiponectin C1Q and collagen domain containing (ADIPOQ), and lipoprotein lipase (LPL), were significantly downregulated (p < 0.01).ConclusionThe expression patterns of miRNAs exhibited significant fluctuations during different development periods of the fat tail, and some of them may participate in the regulation of tail fat deposition by modulating the proliferation and differentiation of preadipocytes.